Cause of Death During Renal Cell Carcinoma Survivorship: A Contemporary, Population-Based Analysis - Yu, Dong-Dong; Chen, Wei-Kang; Wu, Chen-Yu; Wu, Wan-Ting; Xin, Xiao; Jiang, Yu-Li; Li, Peng; Zhang, Ming-Hua (Frontiers in Oncology, 2022)
ABSTRACT BACKGROUND: As the survival rates of patients with renal cell carcinoma (RCC) continue to increase, noncancer causes of death cannot be ignored. The cause-specific mortality in patients with RCC is not well understood. OBJECTIVE: Our study aimed to explore the mortality patterns of contemporary RCC survivors. METHODS: We performed a retrospective cohort study involving patients with RCC from the Surveillance, Epidemiology, and End Results (SEER) database. We used standardized mortality ratios (SMRs) to compare the death rates in patients with RCC with those in the general population. RESULTS: A total of 106118 patients with RCC, including 39630 who died (27%), were included in our study. Overall, compared with the general US population, noncancer SMRs were increased 1.25-fold (95% confidence intervals [CI], 1.22 to 1.27; observed, 11235), 1.19-fold (95% CI, 1.14 to 1.24; observed, 2014) and 2.24-fold (95% CI, 2.11 to 2.38; observed, 1110) for stage I/II, III and IV RCC, respectively. The proportion of noncancer causes of death increased with the extension of survival time. 4273 men with stage Ⅰ/Ⅱ disease (23.13%) died of RCC; however, patients who died from other causes were 3.2 times more likely to die from RCC (n = 14,203 [76.87%]). Diseases of heart was the most common noncancer cause of death (n= 3718[20.12%]; SMR, 1.23; 95% CI, 1.19-1.27). In patients with stage III disease,3912 (25.98%) died from RCC, and 2014 (13.37%) died from noncancer causes. Most patients (94.99%) with stage IV RCC died within five years of initial diagnosis. Although RCC was the leading cause of death (n = 12,310 [84.65%]), patients with stage IV RCC also had a higher risk of noncancer death than the general population (2.24; 95% CI, 2.11-2.38). CONCLUSIONS: Non-RCC death causes account for more than 3/4 of RCC survivors among patients with stage I/II disease. Patients with stage IV are most likely to die of RCC, however, there is an increased risk of dying from septicemia, and suicide cannot be ignored. These data provide the latest and most comprehensive assessment of the causes of death in patients with RCC.